Urgency Of Public Examination As Social Control In Combating Judicial Corruption - Nur Hafizal Hasanah (Fakultas Hukum Universitas Widya Mataram, 2025)
The emergence of a judicial corruption phenomenon, namely corruption carried out by judicial officials, is an irony of a law, because the apparatus who should maintain the legal spirit of the law is actually trapped in betrayal of the law in committing corruption. The existence of public distrust of the underlying legal institution is carried out by public examination, namely supervising judicial institutions by criticizing or testing products produced by judicial institutions The purpose of this study is to examine the urgency of public examination as a social dick in combating judicial corruption and how the legal position of public examination in the judicial system in Indonesia. This research method uses the juridical methodnormative by using the legislation approach and concept analysis approach. The urgency of public examination aims to build public trust in law and law enforcement which is an important aspect in the current Indonesian rule of law. The existence of public examination as a social control aimed at strengthening the accountability of the judicial institution and minimizes the practice of judicial corruption, thus supporting the establishment of the principles of the rule of law and substantive justice. Public examination has not been explicitly regulated in the form of formal binding laws. However, the examination has an indirect normative and legal foundation of the principles of openness, public participation and the right to justice and mastery of judiciary. Keywords: Corruption, Examination, Judicial, Public